Ocular Manisfestations in Xeroderma Pigmentosum; A Series of 20 Patients (Medical Forum Monthly, 2024)
Objective: To assess the various ocular manifestations in xeroderma pigmentosum seen at Eye and Dermatology Department of Chandka Medical College Hospital Larkana.Study Design: Prospective studyPlace and Duration of Study: This study was carried out at two Departments, i.e. at Departments of Dermatology and Ophthalmology of Chandka Medical College larkana from January 2013 to December 2014.Material and methods: Twenty cases were enrolled from outpatient of Eye and Skin Department, Chandka Medical College Hospital Larkana. Patients were subjected to detail history, complete eye and skin examination and relevant investigations.Results: 20 patients, 12(60%) males and 8 (40%) females with xeroderma pigmentosum in a gender ratio of 1.5 : 1 were recruited. All patients had skin freckles and increased sensitivity to sun light. Photophobia and conjunctivitis was seen in 18(90%) cases, keratitis and dry eyes was seen in 12 (60%) cases and 4 (20%) cases had malignancies of lids and conjunctiva proved on biopsy. Our cases belongs to larkana and sukkur division.Conclusion: The present study highlights the eye involvement in xeroderma pigmentosum and thereby early detection of eye disease prevent the malignancies and blindness